Appropriate ultrasonic treatment improves the production of antioxidant peptides by modifying gelatin extracted from yak skin. (25th June 2022) - He, Long; Han, Ling; Wang, Yanru; Yu, Qunli
Summary: The antioxidant peptide was produced from hydrolysis with Bacillus subtilis proteases supplemented with different duration of ultrasound, and the hydrolysis and structural characteristics of yak skin gelatin (YSG) were characterised. Compared with the excessive ultrasonic treatment (10–40 min), the YSG produced by moderate ultrasonic treatment (5 min) had a higher degree of hydrolysis and the DPPH free radical scavenging ability, and ABTS free radical scavenging activity of the hydrolysate was increased. The results showed that ultrasound for 5 min significantly weakened hydrogen bonds and promoted the exposure of hydrophobic groups, resulting in the loosening of collagen structure. Appropriate ultrasonic treatment obviously changed the gelatin structure, as the changes in the decrease of glass transition temperature, the reduction of particle size and the destruction of the surface morphology. These findings showed that moderate ultrasound (5 min) could modify the structure of YSG and, therefore, has great potential in the production of antioxidant peptides. Abstract : This study improved the production of antioxidant peptides through moderate ultrasonic treatment, which was mainly attributed to the sonication‐induced reduction of particle size, improvement of solubility, modification of structure, and reduction of stability of the yak skin gelatin.